2021
DOI: 10.1139/cjce-2020-0144
|View full text |Cite
|
Sign up to set email alerts
|

Creating a performance indicator for temporary housing

Abstract: Most research works have focused predominantly on categorizing temporary houses and have neglected to create an assessment tool for selecting the most optimal temporary housing option based on their performances. This research aims to: (1) investigate the relevant vital indicators affecting the post-disaster temporary house construction process; (2) create a performance indicator (PI) table to help in creating more sustainable and resilient temporary houses; (3) examine each of the existing temporary houses ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Because the affected people are not involved in the site selection process, they may not be willing to live there. Therefore, the site selection process should be done in consultation with stakeholders (Afkhamiaghda, 2021). Furthermore, studies showed that insufficient public participation as a crucial factor could lead to failure in site selection (Cong et al , 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Because the affected people are not involved in the site selection process, they may not be willing to live there. Therefore, the site selection process should be done in consultation with stakeholders (Afkhamiaghda, 2021). Furthermore, studies showed that insufficient public participation as a crucial factor could lead to failure in site selection (Cong et al , 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%